Assessing Children's Implicit Attitudes Using the Affect Misattribution Procedure. Issue 3 (26th May 2016) - Williams, Amanda; Steele, Jennifer R.; Lipman, Corey
Abstract : In the current research, we examined whether the Affect Misattribution Procedure (AMP) could be successfully adapted as an implicit measure of children's attitudes. We tested this possibility in 3 studies with 5- to 10-year-old children. In Study 1, we found evidence that children misattribute affect elicited by attitudinally positive (e.g., cute animals) and negative (e.g., aggressive animals) primes to neutral stimuli (inkblots). In Study 2, we found that, as expected, children's responses following flower and insect primes were moderated by gender. Girls (but not boys) were more likely to judge inkblots as pleasant when they followed flower primes. Children in Study 3 showed predicted affect misattribution following happy-face compared with sad-face primes. In addition, children's responses on this child-friendly AMP predicted their self-reported empathy: The greater children's spontaneous misattribution of affect following happy and sad primes, the more children reported feeling the joy and pain of others. These studies provide evidence that the AMP can be adapted as an implicit measure of children's attitudes, and the results of Study 3 offer novel insight into individual differences in children's affective responses to the emotional expressions of others.